2003
DOI: 10.2337/diacare.26.4.1137
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of an Electrochemical Sensor for Measuring Capillary Blood Ketones by Fingerstick Samples During Metabolic Deterioration After Continuous Subcutaneous Insulin Infusion Interruption in Type 1 Diabetic Patients

Abstract: OBJECTIVE -This study was designed to test the accuracy of capillary ketonemia for diagnosis of ketosis after interruption of insulin infusion. RESEARCH DESIGN AND METHODS-A total of 18 patients with type 1 diabetes treated by external pump were studied during pump stop for 5 h. Plasma and capillary ketonemia and ketonuria were determined every hour from 7:00 A.M. (time 0 min ϭ T0) to 12:00 P.M. (time 300 min ϭ T300). Plasma ␤-hydroxybutyrate (␤-OHB) levels were measured by an enzymatic end point spectrophotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 25 publications
3
90
0
5
Order By: Relevance
“…Our finding of infrequent ketonemia following pump suspension is consistent with prior studies that have shown that pump insulin delivery can be suspended for up to 5 h without producing significant ketonemia. [7][8][9] In studies of sensor-augmented pumps with a low glucose suspend feature (Paradigm VeoÔ; Medtronic Diabetes), no significant ketosis or ketoacidosis has been reported in thousands of 2-h nocturnal pump suspensions. [10][11][12][13] On intervention nights (algorithm operational), glucose levels tended to be lower on nights with pump suspension compared with nights without pump suspension, reflecting that there were lower glucose levels on nights triggering a suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding of infrequent ketonemia following pump suspension is consistent with prior studies that have shown that pump insulin delivery can be suspended for up to 5 h without producing significant ketonemia. [7][8][9] In studies of sensor-augmented pumps with a low glucose suspend feature (Paradigm VeoÔ; Medtronic Diabetes), no significant ketosis or ketoacidosis has been reported in thousands of 2-h nocturnal pump suspensions. [10][11][12][13] On intervention nights (algorithm operational), glucose levels tended to be lower on nights with pump suspension compared with nights without pump suspension, reflecting that there were lower glucose levels on nights triggering a suspension.…”
Section: Discussionmentioning
confidence: 99%
“…The assay range is 0.0-6.0 mmol/L. A previous study reported that the intra-assay coefficients of variation tested on three different levels of β-hydroxybutyrate (low at the mean of 0.43, moderate at 1.08, and high at 3.55 mmol/L) were 10.5, 5.5, and 3.2%, respectively [12].…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Estudos mais recentes têm sugerido que a dosagem capilar de BHB possa também ser extremamente útil para o diagnóstico domiciliar de CAD incipiente, facilitando a recuperação precoce. É recomendada a medida domiciliar de cetonemia no sangue capilar ou cetonúria com fita reagente própria para pacientes com DM1 com hiperglicemia persistente acentuada (≥ 300 mg/dL ou até menos, a critério clíni-co), especialmente na vigência de stress ou quadros infecciosos (40)(41)(42)(43)(44).…”
Section: Cetonemiaunclassified